(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Wireless Sensor Networks (WSNs) have grown in importance in the modern era due to advancements in communication and wireless sensor technology. Wireless sensor networks (WSNs) use gateway routers to transmit data collected from tiny sensor nodes to a large base station (BS) that focuses on environmental, biological, and physical factors. Access this info whenever and anywhere you choose. When sensor nodes have insufficient power, it might shorten the lifespan of a WSN. When it comes to communicating with sensor nodes, more than one routing method is at your disposal. Data transmission uses more electricity. That is why minimizing power consumption in WSNs is crucial. Researchers are continually looking for better data transmission methods to extend the lifespan of WSNs. In this study, we present the E-PEGASIS protocol, which is an extension of the PEGASIS protocol that allows for more efficient data transport in sensor information systems. The suggested method considers the average distance between sensor nodes when establishing chaining and communicating the radio range value of the furthest node to the base station. The next step is for it to configure radio links between nearby nodes. Before continuing to chain with the next node, each sensor node measures its distance to the other end of the connection to make sure data is transferred more effectively. Results from simulations show that the proposed network is more resilient than the LEACH and PEGASIS security protocols.